Manual of soft-tissue management in orthopaedic trauma - Frankle, Mark A.; Volgas, David A. (Thieme Medical Publishers, 2011)
This textbook provides that knowledge applicable in everyday clinical situations, focusing on interdisciplinary treatment strategies and basic soft-tissue techniques. 20 carefully selected case studies further illustrate this comprehensive approach and the complex process of decision making.